Metagenomics analysis revealed the coupling of lignin degradation with humus formation mediated via shell powder during composting. (November 2022) - Ma, Liangcai; Sun, Ru; Yang, Hongxiang; Li, Jixuan; Wen, Xiaoli; Cao, Ziyi; Zhou, Yucheng; Fu, Mengxin; Li, Qunliang
Graphical abstract: Highlights: SP enhanced both Maillard and polyphenol humification pathways. Adding SP significantly promoted lignin degradation and increased HS content. Adding SP resulted in the abundance of Actinobacteria increased. Actinobacteria were key for lignin degradation and humus formation. AA1 and AA3 were the main enzymes to drive lignin degradation and humus formation. Abstract: This study was the first to explore the effect of shell powder (SP) on lignin degradation and humus (HS) formation during composting. The results showed that the treatment group (T) with SP consumed more polyphenols, reducing sugar and amino acids than the control group (CK), especially the rate of reducing sugar consumption in T (50.61 %) was significantly higher than CK (28.40 %). SP greatly enhanced the efficiency of lignin degradation (T:45.47 %; CK:24.63 %) and HS formation (T:34.93 %; CK:20.16 %). The content of HA in T was 12.94 mg/g while CK was 12.06 mg/g. SP maintained a continuous increase in the relative abundance of AA1, AA3 after cooling phase. Meanwhile, T (48.98 %) significantly increased the abundance of Actinobacteria compared with CK (37.19 %). Actinobacteria, AA1 and AA3 were identified as the main factors promoting lignin degradation and HS formation by correlation analysis. Therefore, adding SP could be a novel strategy to improve compost quality.